Estructura de un modelo pedagógico desde el enfoque naturalista de la educación en el Programa De Análisis y Programación de Computadores en la Corporación Instituto de Artes y Ciencias, C. I. A. C (2006)
The following project fulfills a general goal such as: Tending toward the vocational training of an apt professional technician in the technical area of the Programming Computer, capable of providing optimal solutions to the problems which could be presented over the manipulation of the information inside organizations, improving the spirit of the conducting business through which be possible to integrate in a creative way the corporate productive processes. Furthermore, there are two specific objectives: Training fully the student through a curriculum let to the improvement of the interest in the technical development and the freedom structure of expression and participation in the development scenarios. Promoting the participation of the students in the social extension programs and professional groups. Creating a suitable environment to help students adquire knowledge. Generating skill and facilitating the development of actitudes which allow them to practice their habilitéis in a competent way. The frame of reference of the methodology of this research is based on the sociocritical pattern with etnographic projections. Due to the particular features of this project, the etnography was used to observate according to its naturalist conditions